Strategic Importance of the Indo-Pacific and the Bay of Bengal: Navigating Geopolitical Challenges - Ahmad, Syed Misbah Uddin (BIMRAD Journal, 2026)
The Indo-Pacific Region (IPR) has become a key focus of 21st century geopolitics. In its waters, maritime trade, power projection, and strategic rivalry come together. This article examines the geostrategic and economic significance of the Indo-Pacific and the Bay of Bengal, emphasizing how Bangladesh’s maritime position impacts its role in great-power competition. Using realist, liberal, and constructivist theories, the article analyzes power distribution, institutional resilience, and identity politics in the IPR. The study employs a qualitative research approach that combines document analysis, secondary literature review, and interpretive geopolitical mapping to trace the development of alliances, non-traditional security (NTS) issues, and blue economy opportunities. Results indicate that Bangladesh’s balanced diplomacy, maritime modernization, and multilateral engagement enhance its strategic independence within the Indo-Pacific framework. BIMRAD Journal VOLUME 6, ISSUE 1, DEC 2025; PP-1-27